ORGANIZATION OF COMPUTER SCIENCE BASED ON MODULE TECHNOLOGY - Z. Akhmedova; Sodiqjon Muminjonovich Turdaliyev (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides clear and complete information about the organization of computer science based on module technology.